Strategi dan Teknik Penelusuran Informasi Pemustaka di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Mutiarani, Wezi; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThe purpose of this study were (1) for describe Strategy librarian investigation technique in record and library goverment west sumatera, and (2) describe librarian investigation information technique in record and library goverment west sumatera. Librarian and member of the library concering aout research data method with observation, interview and library study in record and library goverment west sumatera. Data analysis do with descriptive. On the strength of data analysis, have as conclusion that in Strategy librarian investigation technique in record and library goverment west sumatera has three strategy: (1) librarian strategy before do invetigation dor information, (2) librarian strategy while do investigation, and (3) librarian strategy in investigation of information, has covered: starting, monitoring, and extracting. Meanwhile, in librarian investigation information technique in record and library goverment west sumaterarefer that while do librarian investigation information using investigation of information gronded word and of inner word.Keywords: library;Â  information literacy; and investigaion information.